Speed breeding is a powerful tool to accelerate crop research and breeding. (January 2018) - Watson, Amy; Ghosh, Sreya; Williams, Matthew; Cuddy, William; Simmonds, James; Rey, María-Dolores; Asyraf Md Hatta, M.; Hinchliffe, Alison; Steed, Andrew; Reynolds, Daniel; Adamski, Nikolai; Breakspear, Andy; et al.
Abstract The growing human population and a changing environment have raised significant concern for global food security, with the current improvement rate of several important crops inadequate to meet future demand1 . This slow improvement rate is attributed partly to the long generation times of crop plants. Here, we present a method called 'speed breeding', which greatly shortens generation time and accelerates breeding and research programmes. Speed breeding can be used to achieve up to 6 generations per year for spring wheat (Triticum aestivum ), durum wheat (T. durum ), barley (Hordeum vulgare ), chickpea (Cicer arietinum ) and pea (Pisum sativum ), and 4 generations for canola (Brassica napus ), instead of 2–3 under normal glasshouse conditions. We demonstrate that speed breeding in fully enclosed, controlled-environment growth chambers can accelerate plant development for research purposes, including phenotyping of adult plant traits, mutant studies and transformation. The use of supplemental lighting in a glasshouse environment allows rapid generation cycling through single seed descent (SSD) and potential for adaptation to larger-scale crop improvement programs. Cost saving through light-emitting diode (LED) supplemental lighting is also outlined. We envisage great potential for integrating speed breeding with other modern crop breeding technologies, including high-throughput genotyping, genome editing and genomic selection, accelerating the rate of crop improvement. Fully enclosed, controlled-environment growth chambers can accelerate plant development. Such 'speed breeding' reduces generation times to accelerate crop breeding and research programmes, and can integrate with other modern crop breeding technologies.